Cytotoxic Effects of Digoxin on Mesenchymal Stem Cells: An in Vitro Study - Hooshang Rafighdoust; Amaneh Mohammadi Roushandeh; Shirin Darabi; Motahareh Mortazavi; Amir Rafighdoust (Negah Institute for Scientific Communication, 2014)
Introduction: Cardiac glycosides such as digoxin or digitoxin are the natural products that are traditionally used to increase cardiac contractile force in patients with heart failure and cardiac arrhythmias. It has been shown that digoxin can directly inhibit the cell proliferation and lead to cell apoptosis. Present study was conducted to analyze the effect of digoxin in the cohorts of mesenchymal stem cells(MSCs) -based therapy. Methods: MSCs were cultured and treated with different concentrations (0.1, 0.5, 1, 5, 7, 10, 15, 20, 30 and 40 μM) of digoxin for 6, 12, 24 and 48 hours. MTT assay was performed to study cell viability and proliferation. Results: After 24 and 48 hours, cell viability was significantly decreased in 20, 30 and 40 μM concentrations (P<0.05), but significant decline in cell viability was observed only in 40 μM after 12 hours (P0.05). Conclusion: It is suggested that digoxin may lead to decline in cell survival ability and increase in cell apoptosis in a dose-time dependent pattern. It is recommended to consider application of glycosoids in concurrence with stem cell therapy.